RADIKALISASI DAN MODERASI : STUDI GERAKAN ISLAM MAINSTREM JAMA’AH ISLAMIYAH DAN NAHDATUL ULAMA DI INDONESIA - abdur rasyid (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
This paper will parse and explain the moderation movement initiated and mobilized by the Islamic organization Nahdhatul Ulama and radical movements conducted by Jama'ah Islamiyah. The focus of this paper will look at the Islamic philosophy and vision (NU and JI) on religious and political relations. This research uses qualitative method with descriptive analysis, that is data used in research and supported by theme-related literatures. The NU moderation movement is a manifestation of ideology formed in many spaces, one of the most important being culture. Contextualization and internalization of the interpretation of the sacred texts namely Al Quran and Hadith, birth concepts such as pluralism and endurance. The earthing of Islamic teachings in accordance with the concept of rahmatan lil alamin existing in the Qur'an can not be a left or right object (moderate). Islam is present as a religion that lays political and Islamic relations as two sides complement each other and maintain their own identity. Islam requires politics and state for the media to develop its teachings in all aspects of community life, while the state needs Islam to safeguard, guard and guide the life of the state and society. On the other hand, Jama'ah Islamiyah known as extremist groups who want a system of state order called